Media Convergence Welcomes Industry 4.0 - Ichsan Adil Prayogi; Nuryah Asri Sjafirah; Evie Ariadne Shinta Dewi (Ikatan Sarjana Komunikasi Indonesia, 2020)
This article discusses how media convergence, as a new era of media in welcoming the industrial revolution, is not working properly. The purpose of this study is to explain how the media today still often create content with profit priority. By using Vincent Mosco's political economy theory and case studies on local media with national networks, the author tries to unravel how the media performs its functions. As a result, even though the media has developed more advanced with the era of digital media, the media is still often used for political interests or other interests through the titles or news content they make. To anticipate this, the general public should equip themselves with the capabilities of media literacy and digital literacy, so that they Â cannot choose a media that is suitable for consumption in the era of industrial revolution 4.0 where the media has developed into digital domain.